Contribution of tourism to economic growth and development in the Caribbean (CTRC BridgetownBB, 1987)
Shows how tourism contributes to economic growth and development in the Caribbean by generating foreign exchange and employment, and alleviating balance of payments deficits and debt. Discusses its contribution to the GNP and argues that the tourist industry not only ensures a stable and secure social and political climate for investors in the region but provides trading links between the Caribbean and the main tourist-generating countries. Discusses constraints to tourism development and recommends immediate policy action. Appendices contain statistical tables on visitor arrivals and expenditure; values of sugar, bauxite, banana and manufacturing exports from the region; balance of payments and employment.
IDS